2007
DOI: 10.1042/bst0350634
|View full text |Cite
|
Sign up to set email alerts
|

RNA dynamics of fertile and infertile spermatozoa

Abstract: The presence of a complex population of mRNAs in human mature spermatozoa is well documented; among them, transcripts of aromatase and ERs (oestrogen receptors) have been described but their significance is not clear. Therefore, to clarify the role of this complex population of mRNAs in human ejaculated sperm, we have isolated on discontinuous density gradients two main fractions from the same sample: high- and low-motile spermatozoa. The levels of different transcripts coding for molecules involved in nuclear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…Therefore, early claims about the presence of RNA in mouse [3], bull [4], rat and human sperm [5] were met with skepticism. However, research over the past decade has provided compelling evidence that mature mammalian sperm contain complex populations of RNAs [1], [2], [6], [7], [8], [9]. These include over 3,000 mRNAs [6], [8], and a heterogeneous population of small and long non-coding RNAs [8], [10], [11], [12], [13], [14], though typically sperm are depleted of intact ribosomal RNAs [6].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, early claims about the presence of RNA in mouse [3], bull [4], rat and human sperm [5] were met with skepticism. However, research over the past decade has provided compelling evidence that mature mammalian sperm contain complex populations of RNAs [1], [2], [6], [7], [8], [9]. These include over 3,000 mRNAs [6], [8], and a heterogeneous population of small and long non-coding RNAs [8], [10], [11], [12], [13], [14], though typically sperm are depleted of intact ribosomal RNAs [6].…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, several groups have independently provided compelling evidence that the transcriptionally and translationally inert mature spermatozoon contain a complex population of RNAs [Carreau et al 2007; Dadoune 2009; Fischer et al 2012; Galeraud-Denis et al 2007; Hamatani 2012; Krawetz 2005; Ostermeier et al 2002; Ostermeier et al 2005a; Ostermeier et al 2005b; Pessot et al 1989]. The functions of the majority of sperm RNAs remain enigmatic although their use in early embryonic development has been proposed [Krawetz 2005].…”
Section: Introductionmentioning
confidence: 99%
“…The functions of the majority of sperm RNAs remain enigmatic although their use in early embryonic development has been proposed [Krawetz 2005]. Many approaches (microarrays, RNA-Seq, RT-PCR) have been applied to identify the potential functions of transcripts retained in sperm [Card et al 2013; Carreau, et al 2007; Jodar et al 2012; Lima-Souza et al 2012; Platts et al 2007; Yang et al 2009]. Success using these technologies is dependent on the quality of the RNA obtained.…”
Section: Introductionmentioning
confidence: 99%
“…These observations of decreased sperm motility in men with aromatase deficiency, together with our data showing a significant decrease of aromatase in immotile human spermatozoa, could suggest that aromatase is involved in the acquisition of sperm motility. In mouse as well as in man it has been shown that estrogens are positively involved in sperm capacitation and acrosome reaction (54). The existence of ERs on the sperm membrane (55) and in the mitochondria (52) is likely to be relevant for a role of estrogens in male gamete motility.…”
Section: Conclusion: Estrogens and Male Fertilitymentioning
confidence: 99%
“…As also suggested by Ostermeier et al (56), the genetic fingerprint of fertile men could include the analysis of mRNA profiles and thus aromatase and ERs may be helpful. Nevertheless, it is clear that further studies are necessary to elucidate the real impact of estrogen on human male reproduction, although it is obvious that several steps are involved (54). Even if numerous estrogentargeted genes remain to be defined, there is now a body of evidence in favor of a positive role for estrogens in male reproduction via genomic and rapid membrane effects (for a review, see Ref.…”
Section: Conclusion: Estrogens and Male Fertilitymentioning
confidence: 99%